A preparation process of silicon nitride ceramic material
By constructing and utilizing the radiation intensity data index of ceramic materials during the insulation process, the problems of poor performance and low porosity caused by uncertainty in the insulation time during the insulation process are solved, and the improvement of material performance and porosity are achieved.
Patent Information
- Application Number
- CN202411884137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the process of preparing silicon nitride ceramic materials, the uncertainty of the insulation time leads to too long or too short pores in the ceramics, resulting in poor material performance and low porosity.
By collecting the radiation intensity data of the blank in the furnace, the thermal synchronization index of the pores, the pore expansion factor and the thermal insulation saturation index are constructed. These indexes are used to control the insulation duration to ensure the appropriate growth of the pores and the stability of the pore wall.
The performance and porosity of silicon nitride ceramic materials are effectively improved, and the pore opening rate is avoided due to the long insulation time and the pore connection problems.
Smart Images

Figure CN119330724B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic preparation, and in particular to a preparation process of a silicon nitride ceramic material. Background Art
[0002] Ceramic material is a solid material made of inorganic non-metallic materials through high-temperature sintering. It has many unique physical and chemical properties such as high melting point, high hardness, high wear resistance, electrical insulation, chemical stability, etc. It is also non-toxic and harmless. It is a green and environmentally friendly material that is widely used in industry, electronics, medical treatment, environmental protection and other fields. And with the development of science and technology, the application field of ceramic materials is constantly expanding.
[0003] In the process of preparing silicon nitride ceramic materials, the raw materials and contents used in the preparation process of different batches may be different, resulting in different insulation time in each preparation process. Therefore, it is necessary to strictly control the insulation time in the insulation process. If the insulation time is too long, the pores in the ceramic have enough time to grow, and the average pore size of the pores gradually increases, causing some pore walls to gradually become thinner, resulting in some pores being connected, resulting in poor performance of the prepared silicon nitride ceramic material; if the insulation time is too short, the pores in the ceramic have not yet been fully formed, resulting in the problem of low open porosity in the prepared silicon nitride ceramic material. Summary of the invention
[0004] In view of the above, it is necessary to provide a preparation process of silicon nitride ceramic materials to improve the performance and open porosity of silicon nitride ceramic materials.
[0005] An embodiment of the present application provides a process for preparing a silicon nitride ceramic material, the process comprising:
[0006] S1: dissolving titanium dioxide and hydroxymethyl cellulose in butanediol, heating and stirring to obtain a mixed solution; adding straw powder to the mixed solution, stirring, drying, calcining under a nitrogen atmosphere, cooling to room temperature, and grinding to obtain modified titanium dioxide;
[0007] S2: mixing the silicon nitride powder, the modified titanium dioxide and nano magnesium oxide uniformly to obtain a mixture;
[0008] S3: adding the mixture into a polyethylene glycol solution, ball milling, drying and sieving the obtained slurry, and compression molding to obtain a blank;
[0009] S4: rapidly heating the blank to 1080° C. in a nitrogen atmosphere, then slowly heating the blank to 1380° C., heating the blank at a preset speed and then holding the temperature, controlling the holding time, and cooling the blank to obtain a porous silicon nitride ceramic material;
[0010] The process of controlling the insulation time is as follows:
[0011] S401: Collecting radiation intensity data of all data points of the blank in the furnace at each moment;
[0012] S402: according to the difference of radiation intensity data of each data point and neighboring data points at each moment, the regional pore thermal synchronization index of each data point is obtained, and all data points are classified by combining clustering algorithm to obtain the pore expansion factor at each moment;
[0013] S403: marking the pore expansion factor at each moment and the previous continuous moments according to the value change at adjacent moments, and obtaining the thermal insulation saturation index at each moment;
[0014] S404: Controlling the heat preservation time according to the heat preservation saturation index at consecutive moments.
[0015] In one embodiment, the mass ratio of the titanium dioxide, the hydroxymethyl cellulose and the straw powder is 1:0.03~0.06:0.13~0.3.
[0016] In one embodiment, the calcination temperature is 460-660° C. and the calcination time is 3.5-5 hours.
[0017] In one embodiment, the mass percentages of the silicon nitride powder, the modified titanium dioxide and the nano magnesium oxide are 74% to 91%, 5% to 20% and 3% to 6% respectively.
[0018] In one embodiment, the particle size of the silicon nitride powder is 0.2 to 10 .
[0019] In one embodiment, the mass concentration of the polyethylene glycol solution is 1% to 10%, and the ball milling time is 3 to 22 hours.
[0020] In one embodiment, the heating at a preset speed is specifically heating to 1520-1680° C. at a heating rate of 1° C. / min.
[0021] In one embodiment, the step of obtaining the pore expansion factor at each moment includes:
[0022] At each moment, the absolute value of the difference between the radiation intensity of each data point and the nearest data point in each preset direction is used as the radiation intensity difference index of each data point in each preset direction; the reciprocal of the sum of the radiation intensity difference index of each data point and the preset parameter adjustment factor greater than zero is calculated, and the sum of the reciprocals of the data point in all directions is used as the regional hole thermal synchronization index of the data point;
[0023] Cluster the data points according to the hole thermal synchronization index of the area described by all data points at each time; calculate the mean value of the hole thermal synchronization index of the area described by all data points in each cluster, and record it as the center value of each cluster;
[0024] Calculate the ratio of the number of data points in the cluster where each data point is located to the number of all data points in the radiation intensity data in the furnace, and record it as the synchronous proportion index of each data point; the expansion significance value of each data point is in an increasing relationship with the synchronous proportion index, and in a decreasing relationship with the center value of the cluster where each data point is located;
[0025] The product of the expansion significance value of each data point at each moment and the regional pore thermal synchronization index is calculated; and the sum of the products of all data points at each moment is taken as the pore expansion factor at each moment.
[0026] In one embodiment, the step of obtaining the thermal insulation saturation index at each moment includes:
[0027] Record the sequence of stomatal expansion factors at each moment and a preset number of moments before as the neighboring stomatal expansion factor sequence at each moment;
[0028] For the neighboring pore expansion factor sequence at each moment, the difference between each element and the previous element is calculated, and the normalized value of the difference of each element at each moment is used as the normalized expansion factor of each element; the sign function is used to form the neighboring pore expansion factor sign sequence at each moment for the difference of all elements at each moment; for the neighboring pore expansion factor sign sequence at each moment, the ratio of the number of elements with the element value of 1 before each element to the number of all elements in the neighboring pore expansion factor sign sequence is used as the growth weight of each element;
[0029] For each moment, the multiplication result of the normalized expansion factor of each element in the neighboring pore expansion factor sequence except the last element and the growth weight of the corresponding element in the neighboring pore expansion factor symbol sequence is calculated, and the sum of the multiplication results of all elements at each moment is taken as the thermal insulation saturation index at each moment.
[0030] In one embodiment, the control of the heat preservation time is specifically:
[0031] The normalized results of the thermal insulation saturation index at each moment are obtained. If the normalized results at consecutive set value moments are greater than or equal to the preset saturation threshold, the insulation process is terminated; otherwise, the insulation process continues.
[0032] This application has at least the following beneficial effects:
[0033] This application mainly analyzes the radiation intensity data of all data points at each time during the insulation process of the ceramic material, providing a data basis for the subsequent control analysis of the insulation time; constructs a regional pore thermal synchronization index to measure the heat conduction characteristics of the pores and the pore walls, effectively reflecting the local temperature uniformity of the silicon nitride ceramic material in the furnace; constructs a pore expansion factor to analyze the uniformity of the overall temperature distribution of the ceramic material in the furnace, reflecting the overall open porosity of the silicon nitride ceramic material during the insulation process; constructs a thermal insulation saturation index to analyze the changing trend of the open porosity, and then judge whether the insulation process should be terminated, solving the problem that the pore walls of the silicon nitride ceramic material become thinner and the pores are interconnected due to the long insulation time during the insulation process, resulting in poor performance and low open porosity of the prepared silicon nitride ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A flow chart of a preparation process of a silicon nitride ceramic material provided in this application;
[0035] Figure 2 Schematic diagram of data collection provided for this application;
[0036] Figure 3 Schematic diagram of clustering effect provided for this application;
[0037] Figure 4 This is a flow chart of the insulation time control provided for this application. DETAILED DESCRIPTION
[0038] In the description of the embodiments of the present application, words such as "exemplary", "or", "for example" and the like are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary", "or", "for example" and the like is intended to present related concepts in a concrete manner.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art in the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0040] It should also be noted that the terms "first" and "second" in this application and its drawings are used to distinguish similar objects, rather than to describe a specific order or sequence. The method disclosed in the embodiments of the present application or the method shown in the flow chart includes one or more steps for implementing the method. Without departing from the scope of protection of this application, the execution order of multiple steps can be interchanged with each other, and some steps can also be deleted.
[0041] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0042] The present application embodiment first proposes a preparation process of silicon nitride ceramic material, which is applied to the technical field of ceramic preparation. Figure 1 , the process comprises the following steps:
[0043] S1: dissolving titanium dioxide and hydroxymethyl cellulose in butanediol, heating and stirring to obtain a mixed solution; adding straw powder to the mixed solution, stirring, drying, calcining under a nitrogen atmosphere, cooling to room temperature, and grinding to obtain modified titanium dioxide.
[0044] In Example 1 of the present application, titanium dioxide and hydroxymethyl cellulose are dissolved in butanediol in a mass ratio of 1:0.03, and then heated to 42°C and stirred to mix evenly to obtain a mixed solution; straw powder is added to the mixed solution in a mass ratio of titanium dioxide to straw powder of 1:0.13, stirred and mixed, and then dried, and then calcined at 460°C for 3.5 hours under a nitrogen atmosphere, cooled to room temperature, and ground to obtain modified titanium dioxide.
[0045] In Example 2 of the present application, titanium dioxide and hydroxymethyl cellulose are dissolved in butanediol in a mass ratio of 1:0.05, and then heated to 45°C and stirred to mix evenly to obtain a mixed solution; straw powder is added to the mixed solution in a mass ratio of titanium dioxide to straw powder of 1:0.15, stirred and mixed, and then dried, and then calcined at 550°C for 4.2 hours under a nitrogen atmosphere, cooled to room temperature, and ground to obtain modified titanium dioxide.
[0046] In Example 3 of the present application, titanium dioxide and hydroxymethyl cellulose are dissolved in butanediol in a mass ratio of 1:0.06, and then heated to 52°C and stirred to mix evenly to obtain a mixed solution; straw powder is added to the mixed solution in a mass ratio of titanium dioxide to straw powder of 1:0.3, stirred and mixed, and then dried, and then calcined at 660°C for 5 hours under a nitrogen atmosphere, cooled to room temperature, and ground to obtain modified titanium dioxide.
[0047] S2: The particle size is 0.2 to 10 The silicon nitride powder, the modified titanium dioxide and nano magnesium oxide are uniformly mixed to obtain a mixture.
[0048] In Example 1 of the present application, the mass proportions of silicon nitride powder, the modified titanium dioxide, and nano magnesium oxide are 74%, 20%, and 6%, respectively.
[0049] In Example 2 of the present application, the mass proportions of silicon nitride powder, the modified titanium dioxide, and nano magnesium oxide are 91%, 6%, and 3%, respectively.
[0050] In Example 3 of the present application, the mass proportions of silicon nitride powder, the modified titanium dioxide, and nano magnesium oxide are 90%, 5%, and 5%, respectively.
[0051] S3: adding the mixed material into a polyethylene glycol solution, ball milling, drying and sieving the obtained slurry, and pressing and molding the slurry to obtain a blank.
[0052] In Example 1 of the present application, the mass concentration of the polyethylene glycol solution is 1%; and the ball milling time is 3 hours.
[0053] In Example 2 of the present application, the mass concentration of the polyethylene glycol solution is 4%; and the ball milling time is 10 hours.
[0054] In Example 3 of the present application, the mass concentration of the polyethylene glycol solution is 10%; and the ball milling time is 22 hours.
[0055] It should be noted that the implementer can determine the size of the blank according to actual needs; this application does not impose any restrictions on this.
[0056] S4: rapidly heating the blank to 1080° C. in a nitrogen atmosphere, then slowly heating the blank to 1380° C., heating at a preset speed and then keeping the temperature, controlling the holding time, and cooling the blank to obtain a porous silicon nitride ceramic material.
[0057] In Example 1 of the present application, the temperature is raised to 1520° C. at a heating rate of 1° C. / min, and the method for controlling the holding time is:
[0058] S401: Collect radiation intensity data of all data points of the blank in the furnace at each moment.
[0059] During the heat preservation process, the infrared high-definition thermal imager continuously collects the radiation intensity data of the blank in the furnace at equal time intervals. The time interval is 10s, which can be flexibly adjusted by the implementer according to the actual situation; the data collection diagram is as follows: Figure 2 shown.
[0060] The value of each data point in the radiation intensity data of the blank in the furnace represents the radiation intensity of the position in the furnace corresponding to the data point, reflecting the temperature of the position in the furnace corresponding to the data point. Since the accuracy of the infrared thermal imager is relatively low, each data point in the obtained radiation intensity data of the furnace corresponds to the temperature of an area on the blank in the furnace. At the same time, the thickness of the pores and the hole wall is relatively small, so an area corresponding to a data point may contain multiple pores and hole walls.
[0061] At this point, the collected radiation intensity data in the furnace is obtained, which can be expressed as follows:
[0062]
[0063] in, represents the radiation intensity data in the furnace at time t, Indicates the radiation intensity at the position in the furnace corresponding to the data point in the mth row and nth column.
[0064] S402: According to the difference in radiation intensity data between each data point and the neighboring data points at each moment, the regional pore thermal synchronization index of each data point is obtained, and all data points are classified by combining a clustering algorithm to obtain the pore expansion factor at each moment.
[0065] During the heat preservation process of ceramic materials, pores will gradually appear in the ceramics. Compared with the pore wall, the pore wall has a higher density and a larger surface area, so the heat conduction efficiency of the pore wall is higher than that of the pore. That is, during the heat preservation process, the temperature at the location of the pore wall is relatively high, and the temperature at the location of the pore is relatively low. If the temperature of a data point in the furnace radiation intensity data is relatively high, it indicates that the area of the pore wall in the area of the furnace blank corresponding to the data point is large, and the area of the pore is small, that is, the pores in this area have not grown completely; if the temperature of a data point in the furnace radiation intensity data is relatively low, it indicates that the area of the pore wall in the area of the furnace blank corresponding to the data point is small, and the area of the pore is large, that is, the pores in this area have grown completely.
[0066] Based on the above analysis, a regional hole thermal synchronization index is constructed to reflect the local temperature uniformity of silicon nitride ceramic materials. The process is as follows:
[0067] The radiation intensity data of each data point of the blank in the furnace corresponds to the radiation intensity of a position in the furnace, so the points adjacent to the data point in the eight directions of the radiation intensity data in the furnace are also adjacent in the furnace. The eight directions are specifically: , , , , , , , .
[0068] The absolute value of the difference in radiation intensity between a data point and the nearest data point in each direction is taken as the radiation intensity difference index of the data point in each direction. The greater the difference in radiation intensity between a data point and its adjacent data points, the greater the temperature difference between the two areas of the blank in the furnace, the greater the difference in the proportion of pores and pore walls in the two areas, and the greater the calculated radiation intensity difference index.
[0069] Calculate the inverse of the sum of the radiation intensity difference index of the data point in each direction and the preset parameter adjustment factor greater than zero, and take the sum of the inverses of the data point in all directions as the regional hole thermal synchronization index of the data point. The regional hole thermal synchronization index reflects the local temperature uniformity of the silicon nitride ceramic material. When the ceramic material is insulated in the furnace, the greater the difference in the area ratio of the pores and the pore walls in the area of the blank in the furnace corresponding to the current data point, that is, the larger the pores or the thicker the pore walls, the more uniform the temperature, and the greater the calculated regional hole thermal synchronization index.
[0070] During the heat preservation process of the ceramic material in the furnace, in order to reflect the overall open porosity of the ceramic material at the current moment, the pore expansion factor is constructed. The process is as follows:
[0071] The regional hole thermal synchronization index of all data points in the radiation intensity data of the furnace at each moment is used as the input of the clustering algorithm, and the clustered data points are output.
[0072] The clustering algorithm used in this embodiment is the K-means clustering algorithm, and the necessary parameter cluster number is 3; in addition, the K-means clustering algorithm is a well-known technology, and the specific process will not be repeated in this application; the implementer can choose other clustering algorithms, and this application does not impose any restrictions on this.
[0073] The clustering effect diagram is shown in the figure below. Figure 3 shown.
[0074] The mean value of the hole thermal synchronization index of all data points in each cluster is calculated respectively, and recorded as the center value of each cluster; the ratio of the number of data points in the cluster where each data point is located to the number of all data points in the radiation intensity data in the furnace is calculated, and recorded as the synchronization proportion index of each data point; the expansion significance value of each data point is in an increasing relationship with the synchronization proportion index, and in a decreasing relationship with the center value of the cluster where each data point is located.
[0075] It should be noted that an increasing (decreasing) relationship indicates a trend in which as one variable increases, another variable also increases (decreases). Common increasing (decreasing) relationships include: linear increasing (decreasing) relationship, exponential increasing (decreasing) relationship, logarithmic increasing (decreasing) relationship, power function increasing (decreasing) relationship, periodic increasing (decreasing) relationship, gradual increasing relationship, etc. This application does not impose any restrictions on this.
[0076] In this embodiment, the ratio of the synchronization proportion index of each data point to the center value of the cluster where each data point is located is used as the expansion significance value. The more data points in the cluster, the more data points have similar situations, the higher the significance of the data points, and the smaller the cluster center value of the cluster where the data point is located, the more likely the blank area in the furnace corresponding to the data point in the cluster is to represent the pore expansion area, so the expansion significance value is larger.
[0077] The sum of the product of the expansion significance value of all data points of the green body at each moment in the furnace and the regional pore thermal synchronization index is taken as the pore expansion factor. The higher the open porosity of the silicon nitride ceramic material in the furnace, the greater the pore expansion factor.
[0078] S403: Marking the pore expansion factor at each moment and the previous continuous moments according to the value change at adjacent moments, and obtaining the thermal insulation saturation index at each moment.
[0079] At the initial moment of the insulation process, pores have not yet formed in the silicon nitride ceramic. At this time, the temperature distribution is relatively stable, and the difference in radiation intensity between adjacent data points is small. As the insulation time increases, the pores in the silicon nitride ceramic material gradually increase, and the pore walls gradually become thinner. Due to the different thermal conductivity efficiencies between the pores and the pore walls, the stability of the temperature distribution decreases at this time, and the difference in radiation intensity between adjacent data points gradually increases. If the insulation time is too long, some of the thinner pore walls may disappear, resulting in multiple pores being interconnected to form a large pore. At this time, the temperature distribution gradually forms a stable degree, that is, the difference in radiation intensity between adjacent data points gradually decreases. At this time, the mechanical strength and toughness of the prepared silicon nitride ceramic material decrease, and cooling in subsequent steps may cause stress concentration, increasing the risk of material cracking. Therefore, in the early stage of pore formation and when the pore walls are thick, the insulation time should be extended. When the pores gradually grow, the pore walls become thinner or even disappear, the insulation should be ended to avoid reducing the performance of the silicon nitride ceramic material.
[0080] Based on the above analysis, a thermal insulation saturation index is constructed to reflect the degree to which the insulation process should be terminated. The process is as follows:
[0081] The sequence of pore expansion factors of the nearest a moments before moment t is recorded as the neighbor pore expansion factor sequence at moment t; in this embodiment, the value of a is 10. It should be noted that if the number of moments before moment t is less than a, the regression filling method is used to fill it up so that the length of the neighbor pore expansion factor sequence is a; the regression filling method is a well-known technology, and the specific process is not repeated in this application; the implementer may also choose other methods for filling, and this application does not limit this.
[0082] The difference between the i+1th element and the ith element in the neighboring pore expansion factor sequence at time t is calculated, and the difference of all elements in the neighboring pore expansion factor sequence at time t is used to form the neighboring pore expansion factor sign sequence at time t using the sign function. Based on this, the element values of the neighboring pore expansion factor sign sequence are only -1, 0, and 1, and the number of elements is one less than that of the neighboring pore expansion factor sequence.
[0083] The difference between the i+1th element and the ith element in the neighboring pore expansion factor sequence is normalized, and the normalized result is recorded as the normalized expansion factor. The larger the difference between the gas expansion factors at two adjacent data collection moments, the greater the pore expansion degree in the silicon nitride ceramic material, and the larger the calculated normalized expansion factor. The normalization processing method includes but is not limited to the Sigmoid function and the Z-score normalization method; this application does not limit this.
[0084] The ratio of the number of elements with a sign of 1 in all elements before the i-th element in the symbol sequence of the neighboring stomatal expansion factor at time t to the number of elements in the sequence is taken as the growth weight of the i-th element in the symbol sequence of the neighboring stomatal expansion factor. As time goes by, the more obvious the expansion trend of the stoma is, the greater the calculated growth weight is.
[0085] The multiplication result of the normalized expansion factor of each element except the last element in the neighboring pore expansion factor sequence at each moment and the growth weight of the corresponding element in the neighboring pore expansion factor symbol sequence at each moment is calculated, and the sum of the multiplication results of all elements at each moment is used as the thermal insulation saturation index at moment t. If the insulation time is too long, the larger the pores and the thinner the pore walls in the silicon nitride ceramic material, the more the temperature uniformity is gradually enhanced, the sooner the insulation process should be terminated, and the larger the calculated thermal insulation saturation index is.
[0086] S404: Controlling the heat preservation time according to the heat preservation saturation index at consecutive moments.
[0087] The thermal insulation saturation index at each moment obtained through the above steps reflects the degree to which the insulation process should be terminated. The thermal insulation saturation index at each moment is normalized to obtain a normalized thermal insulation saturation index. If the normalized thermal insulation saturation index is greater than or equal to the saturation threshold, it indicates that the holes in the ceramic material are more likely to be too large and the pore walls are thinner, and the insulation process should be terminated. In order to avoid misjudgment caused by special circumstances at individual moments, this embodiment uses the normalized thermal insulation saturation index of L consecutive moments to be greater than or equal to the thermal insulation saturation index threshold as the judgment condition for terminating the insulation process, that is, if the normalized thermal insulation saturation index of L consecutive moments is greater than or equal to the thermal insulation saturation index threshold, it indicates that the insulation process should be terminated. Among them, the normalization method in this embodiment adopts the Z-score normalization method; the value of L is 10, and the thermal insulation saturation index threshold is 0.75. Among them, the Z-score normalization method is a well-known technology, and the specific process will not be repeated in this application. It should be noted that since the insulation time is preferably between 2 and 10 hours, the insulation time is controlled after 2 hours. If the insulation time exceeds 10 hours, the insulation is stopped. Figure 4 shown.
[0088] After the heat preservation process is completed, the porous silicon nitride ceramic material can be prepared by cooling the furnace.
[0089] In Example 2 of the present application, the temperature is increased to 1630° C. at a heating rate of 1° C. / min, and the insulation time is controlled by the same method as in Example 1.
[0090] In Example 3 of the present application, the temperature is increased to 1680° C. at a heating rate of 1° C. / min, and the insulation time is controlled by the same method as in Example 1.
[0091] The properties of the silicon nitride ceramic materials prepared in Examples 1 to 3 were tested, and the test results are as follows:
[0092] Example 1: Opening rate is 66%, fracture toughness is 11.5 , the flexural strength reaches 62.5MPa.
[0093] Example 2: The opening rate is 62%, and the fracture toughness is 11 , the flexural strength reaches 60.3MPa.
[0094] Example 3: Opening rate is 67%, fracture toughness is 11.5 , the flexural strength reaches 63.1MPa.
[0095] The embodiment of the present application provides a preparation process of silicon nitride ceramic material, which includes: analyzing the radiation intensity data of all data points of the ceramic material at each time during the insulation process, so as to provide a data basis for the subsequent control analysis of the insulation time; constructing a regional pore thermal synchronization index to measure the heat conduction characteristics of the pores and the pore walls, and effectively reflecting the local temperature uniformity of the silicon nitride ceramic material in the furnace; constructing a pore expansion factor to analyze the uniformity of the overall temperature distribution of the ceramic material in the furnace, and reflecting the overall open porosity of the silicon nitride ceramic material during the insulation process; constructing a thermal insulation saturation index to analyze the change trend of the open porosity, and then judge whether the insulation process should be terminated, thereby solving the problem that the pore walls of the silicon nitride ceramic material become thinner and the pores are interconnected due to the long insulation time during the insulation process, resulting in poor performance and low open porosity of the prepared silicon nitride ceramic material.
[0096] The flowchart and block diagram in the accompanying drawings show the possible architecture, function and operation of the system, method and computer program product according to the embodiment of the present application. In this regard, each box in the flowchart or block diagram can represent a module, a program segment or a part of a code, and the module, a program segment or a part of a code contains one or more executable instructions for realizing the specified logical function. In some alternative implementations, the functions marked in the box can also occur in a different order from the order marked in the accompanying drawings. For example, two continuous boxes can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which can depend on the functions involved. In the description corresponding to the flowchart and block diagram in the accompanying drawings, the operations or steps corresponding to different boxes can also occur in a different order from the order disclosed in the description, and sometimes there is no specific order between different operations or steps. For example, two continuous operations or steps can actually be executed substantially in parallel, and they can sometimes be executed in the opposite order, which can depend on the functions involved. Each block in the block diagrams and / or flowcharts, and combinations of blocks in the block diagrams and / or flowcharts, may be implemented by a dedicated hardware-based system that performs the specified functions or actions, or may be implemented by a combination of dedicated hardware and computer instructions.
[0097] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A process for preparing silicon nitride ceramic material, characterized in that: The process includes the following steps: S1: dissolving titanium dioxide and hydroxymethyl cellulose in butanediol, heating and stirring to obtain a mixed solution; adding straw powder to the mixed solution, stirring, drying, calcining under a nitrogen atmosphere, cooling to room temperature, and grinding to obtain modified titanium dioxide; S2: uniformly mixing silicon nitride powder, the modified titanium dioxide and nano magnesium oxide to obtain a mixture; S3: adding the mixture into a polyethylene glycol solution, ball milling, drying and sieving the obtained slurry, and compression molding to obtain a blank; S4: rapidly heating the blank to 1080° C. in a nitrogen atmosphere, then slowly heating the blank to 1380° C., heating the blank at a preset speed and then holding the temperature, controlling the holding time, and cooling the blank to obtain a porous silicon nitride ceramic material; The process of controlling the insulation time is as follows: S401: Collecting radiation intensity data of all data points of the blank in the furnace at each moment; S402: according to the difference of radiation intensity data of each data point and neighboring data points at each moment, the regional pore thermal synchronization index of each data point is obtained, and all data points are classified by combining clustering algorithm to obtain the pore expansion factor at each moment; S403: marking the pore expansion factor at each moment and the previous continuous moments according to the value change at adjacent moments, and obtaining the thermal insulation saturation index at each moment; S404: controlling the heat preservation time according to the heat preservation saturation index at consecutive moments; The specific steps of obtaining the pore expansion factor at each moment include: At each moment, the absolute value of the difference between the radiation intensity of each data point and the nearest data point in each preset direction is used as the radiation intensity difference index of each data point in each preset direction; the reciprocal of the sum of the radiation intensity difference index of each data point and the preset parameter adjustment factor greater than zero is calculated, and the sum of the reciprocals of the data point in all directions is used as the regional hole thermal synchronization index of the data point; Cluster the data points according to the hole thermal synchronization index of the area described by all data points at each time; calculate the mean value of the hole thermal synchronization index of the area described by all data points in each cluster, and record it as the center value of each cluster; Calculate the ratio of the number of data points in the cluster where each data point is located to the number of all data points in the radiation intensity data in the furnace, and record it as the synchronous proportion index of each data point; the expansion significance value of each data point is in an increasing relationship with the synchronous proportion index, and in a decreasing relationship with the center value of the cluster where each data point is located; Calculate the product of the expansion significance value of each data point at each time and the regional pore thermal synchronization index; take the sum of the products of all data points at each time as the pore expansion factor at each time; The specific steps of obtaining the thermal insulation saturation index at each moment include: Record the sequence of stomatal expansion factors at each moment and a preset number of moments before as the neighboring stomatal expansion factor sequence at each moment; For the neighboring pore expansion factor sequence at each moment, the difference between each element and the previous element is calculated, and the normalized value of the difference of each element at each moment is used as the normalized expansion factor of each element; the sign function is used to form the sign sequence of the neighboring pore expansion factor at each moment for the difference of all elements at each moment; For the neighboring pore expansion factor symbol sequence at each moment, the ratio of the number of elements with element value 1 before each element to the number of all elements in the neighboring pore expansion factor symbol sequence is used as the growth weight of each element; For each moment, the product of the normalized expansion factor of each element except the last element in the neighboring pore expansion factor sequence and the growth weight of the corresponding element in the neighboring pore expansion factor symbol sequence is calculated, and the sum of the multiplication results of all elements at each moment is taken as the thermal insulation saturation index at each moment; The control of the insulation time is specifically as follows: Obtain the normalized result of the thermal insulation saturation index at each moment. If the normalized results at consecutive set value moments are greater than or equal to the preset saturation threshold, the insulation process is terminated; otherwise, the insulation process is continued; The expansion significance value is the ratio of the synchronization proportion index of each data point to the central value of the cluster to which each data point belongs; the heating at a preset speed is specifically heating to 1520~1680℃ at a heating speed of 1℃ / min.
2. A process for preparing a silicon nitride ceramic material according to claim 1, characterized in that: The mass ratio of the titanium dioxide, the hydroxymethyl cellulose and the straw powder is 1:0.03~0.06:0.13~0.
3.
3. A process for preparing a silicon nitride ceramic material according to claim 1, characterized in that: The calcination temperature is 460-660° C. and the calcination time is 3.5-5 hours.
4. A process for preparing a silicon nitride ceramic material according to claim 1, characterized in that: The mass percentages of the silicon nitride powder, the modified titanium dioxide and the nano magnesium oxide are 74% to 91%, 5% to 20% and 3% to 6% respectively.
5. A process for preparing a silicon nitride ceramic material according to claim 1, characterized in that: The particle size of the silicon nitride powder is 0.2 to 10 .
6. A process for preparing a silicon nitride ceramic material according to claim 1, characterized in that: The mass concentration of the polyethylene glycol solution is 1% to 10%, and the ball milling time is 3 to 22 hours.
Citation Information
Patent Citations
Preparation method of porous silicon nitride ceramic material
CN108558412A
Dielectric material of piezoresistor and preparation method of dielectric material
CN119028682A